Improvement of kynurenine aminotransferase-II inhibitors guided by mimicking sulfate esters - Jayawickrama, Gayan S. (PLoS One, 2018)
The mammalian kynurenine aminotransferase (KAT) enzymes are a family of related isoforms that are pyridoxal 5’-phosphate-dependent, responsible for the irreversible transamination of kynurenine to kynurenic acid. Kynurenic acid is implicated in human diseases such as schizophrenia where it is found in elevated levels and consequently KAT-II, as the isoform predominantly responsible for kynurenic acid production in the brain, has been targeted for the development of specific inhibitors. One class of compounds that have also shown inhibitory activity towards the KAT enzymes are estrogens and their sulfate esters. Estradiol disulfate in particular is very strongly inhibitory and it appears that the 17-sulfate makes a significant contribution to its potency. The work here demonstrates that the effect of this moiety can be mirrored in existing KAT-II inhibitors, from the development of two novel inhibitors, JN-01 and JN-02. Both inhibitors were based on NS-1502 (IC(50): 315 μM), but the deliberate placement of a sulfonamide group significantly improved the potency of JN-01 (IC(50): 73.8 μM) and JN-02 (IC(50): 112.8 μM) in comparison to the parent compound. This 3–4 fold increase in potency shows the potential of these moieties to be accommodated in the KAT-II active site and the effect they can have on improving inhibitors, and the environments in the KAT-II have been suitably modelled using docking calculations.